High‐temperature stability of YSZ and MSZ ceramic materials in CaF2–MgF2–MgO molten salt system. Issue 5 (21st December 2017) - Kwon, Sukcheol; Cho, Soo‐Haeng; Nersisyan, Hayk H.; Lee, Jinyoung; Kang, Jungshin; Lee, Jong‐Hyeon
Abstract: The high‐temperature stability of YSZ and MSZ specimens was investigated in CaF2 –MgF2 –MgO molten salt at 1200°C. YSZ was mostly composed of m‐ZrO2 and a small part of YF3 in the early stages. The formation of YF3 was attributed to the chemical reaction between Y2 O3 and MgF2, which can lead to the leaching of Y2 O3 from YSZ. With an increase in exposure time, the degraded surface was coarser, and considerable amount of cracks, pores, and spallations were formed. Furthermore, no Y2 O3 was found up to 120 μm of the YSZ bulk in the early stages. MSZ was composed of t‐ZrO2 after 24 hours. However, the volume fraction of m‐ZrO2 was 72% after 72 hours, and CaZrO3 was formed by the chemical reaction between CaO and ZrO2 after 168 hours. In addition, the volume fraction of m‐ZrO2 was 60% in 2.5 wt% MgO and 49% in 10 wt% MgO. In 5 wt% MgO, CaZrO3 was formed. We demonstrate that the high‐temperature stability of MSZ was better than that of YSZ, and that 10 wt% MgO was much more stable than the other concentrations of MgO.